Pengaruh Perkembangan Teknologi Digital terhadap Peran Notaris - Muhammad Fariz Fadlillah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to determine the influence of digital technology development on the role of notaries, as well as the challenges faced by notaries in dealing with digital technology development. This research uses qualitative research methods. The research data was obtained through in-depth interviews with notaries, legal observers, and users of notary services. The data obtained was analyzed using thematic analysis method. The results showed that the development of digital technology has brought positive and negative influences to the role of notaries. The positive influences include: 1) Increasing the efficiency and effectiveness of notary work 2) Reaching a wider community 3) Improving the quality of notary services. The negative influences include: 1) The emergence of new challenges for notaries 2) Raising the potential for legal violations. This research concludes that the development of digital technology has changed the role of notaries. Notaries are required to continue to innovate and improve their competence in order to face these challenges.